Примем пропущенное число за х :
а) 63 - 45 + х = 63
18 + х = 63
х = 63 - 18
х = 45 - пропущенное число
в) 92 - х + 45 = 92
137 - х = 92
х = 137 - 92
х = 45 - пропущ. число
д) (45 + 12) - х = 45
57 - х = 45
х = 57 - 45
х = 12 - пропущ. число
ж) (х + 73) - 31 = 73
х + 73 - 31 = 73
х + 42 = 73
х = 73 - 42
х = 31 - пропущ. число
б) х - 51 + 51 = 76
х = 76 - пропущ. число
г) 56 - х + х = 56
х может быть любым числом
е) (х + 16) - 16 = 47
х + 16 - 16 = 47
х = 47 - пропущ. число
з) (72 + х)- х = 72
72 + х - х = 72
х может быть любым числом.
Примем пропущенное число за х :
а) 63 - 45 + х = 63
18 + х = 63
х = 63 - 18
х = 45 - пропущенное число
в) 92 - х + 45 = 92
137 - х = 92
х = 137 - 92
х = 45 - пропущ. число
д) (45 + 12) - х = 45
57 - х = 45
х = 57 - 45
х = 12 - пропущ. число
ж) (х + 73) - 31 = 73
х + 73 - 31 = 73
х + 42 = 73
х = 73 - 42
х = 31 - пропущ. число
б) х - 51 + 51 = 76
х = 76 - пропущ. число
г) 56 - х + х = 56
х может быть любым числом
е) (х + 16) - 16 = 47
х + 16 - 16 = 47
х = 47 - пропущ. число
з) (72 + х)- х = 72
72 + х - х = 72
х может быть любым числом.
2)-0,2 (-14t + z - 25y) = 2,8t - 0,2z + 5y
3)(x + 3,2) - (x + 6,4) = -3,2
2.1)-7x + 4x - 8x = -9,9
-11x = -9,9
x = 0.9
2.0,6y - 1,9y - 0,5y = 0,54
-0,8y = 0,54
y = -0.675